2018
DOI: 10.1016/j.kint.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin prevents proteolytic epithelial sodium channel (ENaC) activation and volume retention in nephrotic syndrome

Abstract: Volume retention in nephrotic syndrome has been linked to activation of the epithelial sodium channel (ENaC) by proteolysis of its γ-subunit following urinary excretion of serine proteases such as plasmin. Here we tested whether pharmacological inhibition of urinary serine protease activity might protect from ENaC activation and volume retention in nephrotic syndrome. Urine from both nephrotic mice (induced by doxorubicin injection) and nephrotic patients exhibited high aprotinin-sensitive serine protease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
123
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 48 publications
(71 reference statements)
9
123
0
1
Order By: Relevance
“…Proteinuria, volume retention and subsequent hypertension and/or oedema are hallmarks of the NS and possible mechanisms have been identified previously. The murine model of targeted podocin gene inactivation was shown to develop the entire characteristics of FSGS with NS until the fourth week after induction allowing us to carefully examine renal function in a time‐dependent manner over a longer time period then in animal models of PAN‐induced nephrosis or doxorubicin‐induced NS . We have observed sodium retention, hypertension and gross/unselective proteinuria to occur in a chronologic successive order.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria, volume retention and subsequent hypertension and/or oedema are hallmarks of the NS and possible mechanisms have been identified previously. The murine model of targeted podocin gene inactivation was shown to develop the entire characteristics of FSGS with NS until the fourth week after induction allowing us to carefully examine renal function in a time‐dependent manner over a longer time period then in animal models of PAN‐induced nephrosis or doxorubicin‐induced NS . We have observed sodium retention, hypertension and gross/unselective proteinuria to occur in a chronologic successive order.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two key observations support this hypothesis: firstly, treatment with the ENaC inhibitor amiloride greatly attenuates renal sodium retention in rat and mouse models of nephrotic syndrome. Secondly, inhibiting urinary protease activity by treating mice with aprotinin reduces renal sodium retention to a similar extent as amiloride treatment . As pointed out by Prof. Ehmke, two authors of our study contributed to the publication by Svenningsen et al proposing the concept that in nephrotic syndrome uPA converts aberrantly filtered plasminogen to plasmin which can be readily detected in nephrotic urine.…”
mentioning
confidence: 79%
“…There is substantial experimental evidence for the concept that proteolytic ENaC activation by proteasuria contributes to renal sodium retention in nephrotic syndrome . In particular, two key observations support this hypothesis: firstly, treatment with the ENaC inhibitor amiloride greatly attenuates renal sodium retention in rat and mouse models of nephrotic syndrome. Secondly, inhibiting urinary protease activity by treating mice with aprotinin reduces renal sodium retention to a similar extent as amiloride treatment .…”
mentioning
confidence: 96%
“…Contrary to the classical view of altered fluid distribution second to a low plasma oncotic pressure, accumulating evidence suggest that oedema formation in NS is because of the aberrant renal sodium retention . It has been shown that pharmacologic blockade of the epithelial sodium channel (ENaC) using amiloride can prevent sodium retention and relieve nephrotic oedema in both rats, mice and humans . As aldosterone is typically in normal range or suppressed in NS, possibly after a variable and short initial increase, the question is what activates ENaC in NS?…”
mentioning
confidence: 97%
“…Proteolytic activation of ENaC by filtered proteases has emerged as a new concept and several serine proteases have been shown to cleave and activate ENaC . A number of studies have shown that NS is associated with increased urinary excretion of active serine proteases, and the previous study by Bohnert et al was the first to document, in a mouse NS model, that the broad‐spectrum serine protease inhibitor aprotinin attenuates sodium retention. This seminal observation indicates that serine protease activity contributes to nephrotic sodium retention in mouse NS ; however, the importance of the individual protease(s) remains to be clarified.…”
mentioning
confidence: 99%